Proteomics-identified Bvg-activated autotransporters protect against bordetella pertussis in a mouse model. - Daan de Gouw; Marien I de Jonge; Peter W M Hermans; Hans J C T Wessels; Aldert Zomer; Alinda Berends; Catherine Pratt; Guy A Berbers; Frits R Mooi; Dimitri A Diavatopoulos (PLoS ONE, 2014)
Pertussis is a highly infectious respiratory disease of humans caused by the bacterium Bordetella pertussis. Despite high vaccination coverage, pertussis has re-emerged globally. Causes for the re-emergence of pertussis include limited duration of protection conferred by acellular pertussis vaccines (aP) and pathogen adaptation. Pathogen adaptations involve antigenic divergence with vaccine strains, the emergence of strains which show enhanced in vitro expression of a number of virulence-associated genes and of strains that do not express pertactin, an important aP component. Clearly, the identification of more effective B. pertussis vaccine antigens is of utmost importance. To identify novel antigens, we used proteomics to identify B. pertussis proteins regulated by the master virulence regulatory system BvgAS in vitro. Five candidates proteins were selected and it was confirmed that they were also expressed in the lungs of naïve mice seven days after infection. The five proteins were expressed in recombinant form, adjuvanted with alum and used to immunize mice as stand-alone antigens. Subsequent respiratory challenge showed that immunization with the autotransporters Vag8 and SphB1 significantly reduced bacterial load in the lungs. Whilst these antigens induced strong opsonizing antibody responses, we found that none of the tested alum-adjuvanted vaccines - including a three-component aP - reduced bacterial load in the nasopharynx, suggesting that alternative immunological responses may be required for efficient bacterial clearance from the nasopharynx.